Kody geopolityczne w szkicach politycznych Józefa Conrada Korzeniowskiego = Geopolitical codes in Joseph Conrad Korzeniowski?s political novels - Kucharska-Dziedzic, Anita (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Joseph Conrad Korzeniowski, an outstanding Polish writer living in the British Empire, remained a Polish patriot. The outbreak of the First World War meant a change in the political situ?ation in Europe, and thus the chance for Poland to regain sovereignty. Polish state did not exist for over a hundred years after the partition made by Germany, Austria and Russia. Conrad devoted two political sketches to the analysis of the situation and prospects of the Polish independence.
Keywords: Conrad, Joseph (właści. Korzeniowski, Józef Teodor Konrad; pisarz; 1857-1924); szkice polityczne; I (pierwsza) wojna światowa; political novels; First World War